USM HOCKEY TURF RECEIVES GLOBAL RECOGNITION FROM INTERNATIONAL HOCKEY FEDERATION (FIH) - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 20 March 2016 – It is another proud and historic moment at Universiti Sains Malaysia (USM) when its Hockey Stadium turf received international recognition from the International Hockey Federation (FIH).